2011
DOI: 10.3113/fai.2011.1023
|View full text |Cite
|
Sign up to set email alerts
|

Classification and Treatment of Supramalleolar Deformities

Abstract: Supramalleolar osteotomies can be effective for the treatment of early and midstage asymmetric arthritis of the ankle joint. However, certain subgroups have a tendency towards a worse outcome and may require additional surgery. Therefore preoperative distinction of different subgroups is helpful for determination of additional procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
138
2
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(144 citation statements)
references
References 17 publications
0
138
2
4
Order By: Relevance
“…Recently, corrective osteotomies to realign the hindfoot in patients suffering from asymmetric ankle arthritis have been introduced [13][14][15][16]. The goal of these procedures is to redirect forces transmitted across the hindfoot and to shift the loading axis into the area of healthy cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, corrective osteotomies to realign the hindfoot in patients suffering from asymmetric ankle arthritis have been introduced [13][14][15][16]. The goal of these procedures is to redirect forces transmitted across the hindfoot and to shift the loading axis into the area of healthy cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…We based the decision to perform the fibular osteotomy on the pre- and intraoperative evaluation. When the TC angle is decreased more than 5° compared with the contralateral side, which indicates a longer fibula or varus change, a fibular osteotomy may facilitate the reduction of the tibial plafond and talus [19]. Stufkens et al [6] reported that creating a supramalleolar valgus deformity would not cause a shift in contact towards the lateral side of the tibiotalar joint, and the restricting role of the fibula was revealed when an osteotomy was performed.…”
Section: Discussionmentioning
confidence: 99%
“…The role of TT in SMOT is highly controversial. Some authors have reported a significant decrease of the TT [4, 7, 8, 11, 17]; however, others have not [3, 12, 15, 19]. Tanaka et al [12] reported that in all patients with a preoperative TT greater than 10°, the joint space did not return to normal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 The medial and lateral approach is based on the amount of correction desired. 26 The medial opening wedge osteotomy has the advantages of using a simple approach, ease of bone cuts, and no resultant limb length discrepancy. The lateral closing wedge osteotomy allows for ease of fixation, no graft requirement, reliable and rapid healing, and no possibility of medial joint load increase.…”
mentioning
confidence: 99%